APPLICATION OF BRUSSELS II BIS REGULATION IN EXERCISING THE RIGHT OF ACCESS TO A CHILD BY EXTENDED FAMILY MEMBERS - Dragišić, Radmila (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
In this paper, we explore the sources of European Union Law that regulate one segment of parental responsibility – the right to contact with the child. Our research concerns the transition from the conventional (interstate) regulation of the field of judicial cooperation for marital disputes and the issue of parental responsibility to the regulation carrie out by the institutions of the European Union, with special attention paid to the Brussels II bis Regulation. We briefly point out its relationship with the Hague Convention on the Civil Aspects of International Child Abduction, the Hague Convention on Jurisdiction, Applicable Law, Recognition, Enforcement and Cooperation in the Field of Parental Responsibility and Measures for the Protection of Children, and other international sources of law, while we deal in more detail with its relationship with the Brussels II bis recast Regulation, which will apply from 1 August 2022. In addition, we analyze the first case in which the Court of Justice of the European Union decided on the application of the Brussels II bis Regulation at the request of granparents to exercise the right to contact with the child, in terms of whether the competent court should decide on how to exercise such determined on the basis of the said regulations or on the basis of the rules of private international law of the member states. This paper is useful for the professional and scientific community because, among other things, it deals with the issue of justification of adopting a special source of law that would regulate the issue of mutual enforcement of court decisions on the rights of contact with children, as proposed by the French Republic, initially guided by the child’s fundamental right to contact with both parents.